Chromosome configurations of buffalo oocytes matured in-vitro - Das, S K; Chauhan, M S; Palta, P; Tomer, O S (The Indian Journal of Animal Sciences, 2012)
Oocytes aspirated from slaughterhouse buffalo ovaries were cultured in-vitro. After 24 hr of culture the oocytes were fixed and stained with Giemsa stain and analyzed for chromosome configuration. The appearance of various chromosome configurations was documented. Out of 125 oocytes, 25 (20%), 3 (2.4%), 4 (3.2%), 9 (7.2%), 1 (0.8%), 2 (1.6%), 16 (12.8%) and 65 (52.0%) oocytes were at germinal vesicle, condensing chromosome-I, condensing chromosome-II, early diakinesis, diakinesis, anaphase-I, telophase-I and metaphase-II stages, respectively. When oocytes at telophase-I and metaphase-II were pooled to express nuclear maturation, 64.8% oocytes showed nuclear maturation in-vitro.